2014
DOI: 10.4103/0973-1075.132629
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a quality of life questionnaire for Iranian patients with esophageal cancer

Abstract: Introduction:Evaluation of quality of life is very important in cancer patients. Esophagus-specific quality of life questionnaire (QLQ-OES18) is a disease-specific questionnaire for assessing quality of life in esophageal cancer (EC). So we aimed to translate and evaluate the reliability and validity of the QLQ-OES18 when applied to Iranian patients.Materials and Methods:This study was designed as cross-sectional study on 62 newly confirmed EC in two referral hospital in Tehran, Iran. Reliability of the subsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Despite all the progresses made in clinical pharmacology, proper control of pain in this case is still under discussion. 19,20 Therefore, the aim of this study was to compare the effect of sublingual buprenorphine with injectable morphine on the reduction of pain associated with bone metastasis in cancer patients. The findings of this study showed the efficacy of sublingual buprenorphine in increasing the duration of analgesia and reducing the amount of pain more than intravenous morphine, as well as reduction of the drug side effects and its deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the progresses made in clinical pharmacology, proper control of pain in this case is still under discussion. 19,20 Therefore, the aim of this study was to compare the effect of sublingual buprenorphine with injectable morphine on the reduction of pain associated with bone metastasis in cancer patients. The findings of this study showed the efficacy of sublingual buprenorphine in increasing the duration of analgesia and reducing the amount of pain more than intravenous morphine, as well as reduction of the drug side effects and its deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of cancer quality-of-life questionnaire-esophageal cancer (OES-18) module was used to evaluate the symptoms of patients at one month after surgery ( 7 ). One point refers to ‘no’, 2 points refer to ‘a little bit’, 3 points refer to ‘considerable’ and 4 points refer to ‘very’.…”
Section: Methodsmentioning
confidence: 99%